Vetiver Root Extract as a Biopesticide Against Callosobruchus maculatus F., insect destructive of cowpea seeds (Vigna unguiculata L. Walp.) in stock - Dyno, Nambavelo; Sambany, Manjovelo Christian; Nicole, Ravelomanantsoa Ramanambe; Koto-Te-Nyiwa, Ngbolua Jean Paul; Baholy, Robijaona Rahelivololoniaina (Budapest International Research and Critics University, 2025)
This investigation rigorously assessed the bioinsecticidal potential of methanolic root and leaf extracts derived from Vetiveria zizanioides sourced from three distinct Malagasy chemotypes (Sambava, Fianarantsoa, and Tsiroamandidy). The primary goal was to validate a sustainable, botanical alternative for preserving stored cowpea (Vigna unguiculata) against the destructive pest, Callosobruchus maculatus. The vetiver root extracts demonstrated potent, dose-dependent efficacy across all bioassays. Specifically, at concentrations of 60 μl/l of air or higher, the extracts induced complete adult mortality within 72 hours via contact, and nearly total mortality within 48 hours via fumigation. The Tsiroamandidy chemotype proved particularly efficacious, achieving total mortality by the second day at the maximum dose. Critically, the extracts exhibited profound ovicidal activity, resulting in zero egg hatchability even at the minimum concentration of 10 μl/l, completely suppressing reproduction. This decisive biological action translated into significant commodity protection: seed weight loss, which was 25% in untreated controls, was virtually eliminated at the 60 μl/l threshold, consequently preserving seed quality and germination viability. In sharp contrast, the leaf extracts showed severely limited efficacy, achieving a maximum mortality of only 40% even at the highest tested dose. These findings conclusively validate the vetiver root extract as a highly promising, natural biopesticide for the sustainable management of C. maculatus.